Tindak Tutur Dalam Novel Home Sweet Loan Karya Almira Bastari - Yulizar, Meri; Ariani, Zesi; Munawarah, Intan (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
This research aims to examine the types and factors that influence the speech acts of characters in the novel Home Sweet Loan by Almira Bastari. This study used descriptive qualitative method. The data in research is in the form of words, sentences, paragraphs, or dialogue that are in accordance with the research objectives. The main data source is the novel Home Sweet Loan published by Gramedia Pustaka Utama in February 2022. Data collection techniques were carried out using reading and note-taking techniques. The research results reveal that in the novel Home Sweet Loan there are three types of speech acts, namely locution, illocution, and perlocution. Locutionary speech acts are divided into statements, questions and commands. Illocutionary speech acts involve assertive, directive, commissive, and expressive. Perlocutionary speech acts include various forms such as denying, correcting, prohibiting, nodding, depressed, and regretful. Apart from that, the research results also show the factors that influence the speech acts of characters in the novel. These factors are the speaker, the purpose of the speech, the situation, the context, the path, the media, and the event. This research provides in-depth insight into the dynamics of speech acts in the context of the novel "Home Sweet Loan" and contributes to further understanding of the use of language and communication in literary works